Transport of metal ions through cellulose fiber supported solid membrane into tributyl phosphate containing mixed solvents - Gaikwad, Abaji G. (Chemical and Biochemical Engineering Quarterly, 2011)
A novel cation exchange fiber supported solid membrane was developed for transport of cobalt, manganese and nickel metal ions. Fiber supported solid membrane was prepared by chemically modifying the cellulose fibers with citric acid. In the fiber supported solid membrane, the diffusion by capillary action by keeping the liquid phase in the porous solid fiber and ion exchange mechanism were used for the effective transport of metal ions. The experimental variables examined were concentration of metal ions (10(-2) to 10(-4) mol L-1) in the source solution, mixed solvent composition (phi = 20 % TBP, acetone or tetrahydrofuran or 1,4-dioxane or methanol or ethanol or 2-propanol 10 to 60 % and HCl (1 to 2 mol L-1) in the receiving phase and stirring speed (40-120 rpm) of the bulk source and receiving phase. The enrichment of concentration of cobalt, manganese and nickel metal ions was observed from the dilute solutions.
Keywords: binary of mixtures of metal ions; cobalt; extraction; fiber supported solid membrane; ion exchange; manganese and nickel metal ions; stripping